Strengths, Weaknesses, Opportunities, and Threats (SWAT) Analysis Majelis Taklim Dalam Upaya Membentuk Masyarakat Religius Di Kecamatan Sukajadi Pekanbaru - Yanti, Yanti; Murniati, Andi; Murny, Murny; Arnel, Iskandar; Irwandra, Irwandra; Indra, Adam Malik; Nasrul, Nasrul (Kutubkhanah, 2023)
This research aims to determine the Strengths, Weaknesses, Opportunities, and Threats (SWAT) Analysis of the Majelis Taklim in its efforts to form a religious community in Sukajadi District, Pekanbaru. This type of research is quantitative and qualitative. Data collection techniques used questionnaire techniques, short entries and interviews. For this type of quantitative research, the author uses qualitative descriptive data analysis techniques with percentages, meanwhile for qualitative research, the researcher uses the Miles and Hubermen model data analysis techniques. The results of the research and discussion are as follows: 1. The Strengths of the Majelis Taklim lie in aspects; a. number of Majelis Taklim, b. access to mosques and prayer rooms, c. ownership of a Management Decree (SK) as legitimacy in the management of the Majelis Taklim, d. condition of the Taklim Assembly facilities, e. The period of existence of the Majelis Taklim. 2. Weaknesses (Weaknesses) of the Taklim Council lie in aspects; management or governance, for example the absence of a Majelis Taklim management meeting, this is caused by a lack of experience in participating in organizational management or governance training for the Majelis Taklim. 3. Opportunities, the Majelis Taklim administrators can utilize and collaborate with various cross-institutions and agencies. 4. Threats (Threats) for the Majelis Taklim, the urgency does not come from outside, but rather from the condition of the congregation, namely; a. level of awareness or motivation of the congregation in guiding the science assembly, b. The congregation's busyness in fulfilling life's demands, especially in the economic sector, is the cause of absence from various activities held by the Majelis Taklim